APPLYING k-SEPARABILITY TO COLLABORATIVE RECOMMENDER SYSTEMS - Alexandridis, Georgios; Siolas, Georgios; Stafylopatis, Andreas (International Journal on Artificial Intelligence Tools, 2012)
Most recommender systems have too many items to propose to too many users based on limited information. This problem is formally known as the sparsity of the ratings' matrix, because this is the structure that holds user preferences. This paper outlines a Collaborative Filtering Recommender System that tries to amend this situation. After applying Singular Value Decomposition to reduce the dimensionality of the data, our system makes use of a dynamic Artificial Neural Network architecture with boosted learning to predict user ratings. Furthermore we use the concept of k-separability to deal with the resulting noisy data, a methodology not yet tested in Recommender Systems. The combination of these techniques applied to the MovieLens datasets seems to yield promising results.